Menakar Ulang Besaran Persentase Ambang Batas Parlemen yang Konseptual di Indonesia - Tazakka, Wijdan Daurut (SIYASI: Jurnal Trias Politica, 2025)
This research aims to provide legal certainty and a conceptual basis for determining the percentage threshold for parliamentary representation. (parliamentary threshold). The method used in this research is normative juridical (law-normative) relying on literature: books, journals, laws, Constitutional Court decisions, and the internet as the analytical tools in this study. Basically, Indonesia has quite a number of political parties. Viewed from the electoral contests from 1999 to the 2024 elections, according to Satori, Indonesia falls into the category of an extreme multi-party system. With an average of 5 or more relevant political parties in Parliament, this impacts government and political stability. Looking at its history, Indonesia has already responded to this and intends to simplify the party system in parliament. Starting from the implementation of the electoral threshold and parliamentary threshold, this is one of the government’s steps towards achieving a simple multiparty system. However, it becomes a problem when the threshold numbers, especially the parliamentary threshold, increase year by year, from 2.5%, 3%, to the current 4%. However, the attainment of these percentage figures lacks a conceptual basis, as they are merely the result of agreements between political parties. Therefore, this research discusses the formulation to obtain the ideal percentage figure using Taagepera’s theory, and the ideal figure in Indonesia according to Taagepera’s theory is 1%.